Case Report: Rare Case of Synchronous Neck Metastasis From Metachronous Bilateral Renal Cell Carcinoma - Dai, Jun; Fang, Chen; Yang, Xiaoqun; Huang, Xin; He, Wei; Wang, Chenghe; Zhao, Juping; Sun, Fukang (Frontiers in Oncology, 2021)
Renal cell carcinoma (RCC) is a malignant tumor that can metastasize easily. Hence, many patients have already developed metastasis when they are diagnosed. It is also one of the most common tumors that metastasize to the head and neck through ex-tranodal disease. Herein, we reported a case of a 53-year-old man with cervical metas-tasis from bilateral RCC. Interestingly, primary renal sites such as mucinous tubules and spindle cell carcinoma (MTSCC) and papillary renal cell carcinoma (PRCC), and cervical metastases (squamous cell carcinoma) share the same subclones with different morphologies, which was first reported in RCCs to the best of our knowledge. This case suggests that genotype analysis can be a powerful supplementary examination for clinical histopathological diagnosis. Gene detection has great significance for the accurate diagnosis and treatment of RCC metastasis or multiple lesions.